Increasing STEM Transfer Readiness Among Underrepresented Minoritized Two-Year College Students: Examining Course-Taking Patterns, Experiences, and Interventions - Sansing-Helton, Bethany; Coover, Gail; Benton, Charles E. (Frontiers in Education, 2021)
There is a strong need in the United States to increase the size and diversity of the domestic workforce trained in science, technology, engineering, and math (STEM). With almost half of all students that earn a baccalaureate degree enrolling in a 2-year public college at some point, the nation’s 2-year colleges provide great promise for improving the capacity of the STEM workforce for innovation and global competition while addressing the nation’s need for more equity between groups that have been historically included and those that have been economically and politically disenfranchised. Almost half of underrepresented minoritized (URM) students begin their post-secondary education at 2-year colleges yet their transfer rates within 5 years are only 16%. This study describes interventions put in place at a 2-year college to support increased transfer rates and STEM transfer readiness for URM STEM-interested students. The program studied, in place from 2017 through 2020, had an overall transfer rate of 45%. Analysis of administrative, transcript, and student survey data connects the program interventions to the existing research on STEM momentum and other research on URM STEM transfer success. Ultimately, this study identifies potential leading indicators of transfer readiness, providing much needed documentation and guidance on the efficacy and limitations of interventions to improve upward STEM transfer.